Politics of development : Puerto Rico's Caribbean program. - GRUSKY, Sara L. (1994)
Examines how the Caribbean Development Program (CDP) became part of Puerto Rican policy, and notes that it has been instrumental in deepening the integration of the Caribbean into the US economy. Argues that the major beneficiaries of Section 936 money have not been small businesses in the region but the large and financially viable US corporations. Shows how the fate of the CDP is being determined by changing US priorities.